Analisis Pendapatan Petani Kopi Arabika Di Garut Jawa Barat - Rakka Rezkie Surahman; Ernah (lembaga penelitian universitas swadaya gunung jati, 2024)
Coffee is one of the mainstay plantation commodities for Indonesian agriculture. Coffee plantations have quite high export opportunities and potential to be developed in Indonesia, therefore the demand for coffee in both the domestic and international markets is quite high. The high market demand for coffee commodities cannot be separated from the various problems faced by coffee farmers, including the low quality of coffee produced by farmers who are members of farmer groups, which can affect the income of farmers in the Karya Mandiri Farmer Group. For this reason, this research aims to analyze income. coffee farming. Based on the results of research conducted, the average income of coffee farmers in the Karya Mandiri Farmers Group is IDR 21,826,900 per year or IDR 1,818,908 per month, besides that the coffee farming run by the Karya Mandiri Farmers Group is profitable, where the R/C ratio which is more than one.Keywords : Farmer, Coffee, Revenue, Garut, West Java